Ultrahigh-pressure sealing ring for electrolytic bath and preparation method thereof

By using a double-layer structured sealing ring for electrolytic cells, and employing hydrogenated nitrile rubber and fluororubber composite materials and a segmented vulcanization process, the problems of easy deformation, aging, and hydrogen embrittlement of traditional sealing rings under ultra-high pressure are solved, achieving high-efficiency sealing and corrosion resistance under ultra-high pressure of 70MPa.

CN120926265APending Publication Date: 2025-11-11HYDROGEN SEA TECHNOLOGY (HAINAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511097789.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Traditional sealing rings are prone to deformation, aging, and leakage under ultra-high pressure environments. Existing combined sealing structures have short lifespans, high frictional resistance, and a high risk of hydrogen embrittlement under high pressure, and cannot effectively prevent hydrogen molecule penetration.

Method used

The sealing ring for the electrolytic cell adopts a double-layer structure, including a pressure-resistant support layer and a sealing bonding layer. It uses hydrogenated nitrile rubber and fluororubber composite as the matrix material, controls the crosslinking density through a segmented vulcanization process, and combines carbon nanotubes and gas-phase SiO2 to enhance the material properties, so as to achieve a tight fit with the metal skeleton ring.

Benefits of technology

It maintains sealing integrity under ultra-high pressure of 70MPa, has a low leakage rate, long service life, good chemical corrosion resistance, and elastic deformation to offset external pressure, meeting the working requirements under high pressure environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120926265A_ABST
    Figure CN120926265A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer sealing materials, and particularly relates to an ultrahigh-pressure sealing ring for an electrolytic bath and a preparation method of the ultrahigh-pressure sealing ring. A sealing attaching layer and a small polar plate which are stacked are embedded in the inner ring of the compression-resistant supporting layer; a second metal framework ring is arranged in the sealing attaching layer in a wrapped mode. The small polar plate and the large polar plate arranged on one side of the metal framework ring jointly clamp and fix the sealing fitting layer; wherein the hardness of the compression-resistant supporting layer ranges from 60 Shore A to 75 Shore A; the compression-resistant supporting layer is prepared from the following components in parts by mass: 60 parts of hydrogenated butadiene-acrylonitrile rubber, 40 parts of fluororubber, 10-15 parts of gas-phase SiO2, 3-5 parts of carbon nanotubes, 1.5-2.5 parts of a peroxide vulcanizing agent, 2-3 parts of an assistant crosslinking agent and 2-5 parts of a processing aid; and the hardness of the sealing and attaching layer is not lower than 85 Shore A.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer sealing materials technology, specifically relating to an ultra-high pressure sealing ring for electrolytic cells and its preparation method. Background Technology

[0002] Traditional single-material sealing rings (such as O-rings and U-rings) are prone to extrusion deformation, material aging, or seal failure under ultra-high pressure (≥70MPa) conditions. Existing combined sealing structures (such as Step seals and Glyd rings) are mostly designed for medium and low pressure (≤40MPa), but their leakage rate is >0.5mL / min at 70MPa. They also suffer from short lifespan and high frictional resistance under high pressure. Furthermore, the thermal cycling effect and temperature fluctuations (80-150℃) accelerate the aging of traditional sealing materials. There is also the risk of electrochemical corrosion, as the hydrogen diffusion coefficient of the metal reinforcement layer in the environment is >10. -11 m 2 Hydrogen embrittlement is likely to occur at / s.

[0003] Currently, high-voltage electrolytic cell sealing materials face three major technical barriers: First, traditional hydrogenated nitrile butadiene rubber (HNBR) exhibits severe stress relaxation under 70MPa / 100℃ conditions, with a compression set rate exceeding 40% (ISO 815 standard), leading to a continuous decrease in the contact pressure at the sealing interface; second, while pure fluororubber (FKM) systems have corrosion resistance advantages, their hydrogen permeability is >5×10⁻⁶. -12 cm 3 ·cm / cm 2 The ·s·Pa (ASTM D1434) standard cannot effectively prevent the risk of hydrogen embrittlement caused by hydrogen molecule penetration; thirdly, commercially available high-end competing products (such as Parker 70-75) have a leakage rate of more than 0.1 mL / min after 500 pressure cycles, revealing the defect of insufficient dynamic sealing stability.

[0004] High-pressure sealing requires high material compatibility. Mixing different raw materials cannot solve the defects of each material and will reduce the overall performance of the sealing ring. Therefore, how to overcome the incompatibility of sealing materials in the 70MPa ultra-high pressure environment of the electrolytic cell is a technical problem that urgently needs to be solved in this field.

[0005] It should be noted that the information disclosed in this background section is only for understanding the background technology of the present application concept, and therefore, the above description is not considered to constitute prior art information. Summary of the Invention

[0006] This disclosure provides at least one ultra-high pressure sealing ring for an electrolytic cell and its preparation method.

[0007] In a first aspect, embodiments of this disclosure provide a sealing ring for an electrolytic cell, comprising: a first metal skeleton ring and a compression-resistant support layer wrapped around its surface; the inner ring of the compression-resistant support layer is embedded with a stacked sealing bonding layer and a small electrode plate; a second metal skeleton ring is wrapped within the sealing bonding layer; the small electrode plate and a large electrode plate disposed on one side of the metal skeleton ring clamp and fix the sealing bonding layer; wherein the hardness of the compression-resistant support layer is in the range of 60–75 Shore A; the compression-resistant support layer comprises the following components by mass: 60 parts hydrogenated nitrile rubber, 40 parts fluororubber, 10–15 parts fumed SiO2, 3–5 parts carbon nanotubes, 1.5–2.5 parts peroxide vulcanizing agent, 2–3 parts co-crosslinking agent, and 2–5 parts processing aid; the hardness of the sealing bonding layer is not less than 85 Shore A, and its compression set is ≤25%.

[0008] In one optional embodiment, the hardness range of the sealing adhesive layer is 85-95 Shore A; the sealing adhesive layer comprises the following components by weight: 55 parts hydrogenated nitrile rubber, 45 parts fluororubber, 20-30 parts fumed SiO2, 4-8 parts carbon nanotubes, 1-3 parts anti-aging agent, 2.5-3.5 parts peroxide vulcanizing agent, 3-5 parts co-crosslinking agent, 1-3 parts crosslinking agent, 3-8 parts acid absorbent, and 0.5-2 parts processing aid.

[0009] In one optional embodiment, the thickness ratio of the compression-resistant support layer to the sealing bonding layer is not less than 3:1.

[0010] In one optional embodiment, the hydrogenated nitrile rubber has a hydrogenation degree of not less than 94%, wherein the acrylonitrile content is not less than 34%, and the Mooney viscosity ML(1+4) at 100°C is 40-60; the fluororubber includes vinylidene fluoride-hexafluoropropylene copolymer fluororubber with a fluorine content of not less than 66%.

[0011] In one alternative embodiment, the anti-aging agent comprises a 2,2,4-trimethyl-1,2-dihydroquinoline polymer, the acid absorbent comprises highly active magnesium oxide, and the processing aid comprises perfluoropolyether oil.

[0012] Secondly, this disclosure also provides a method for preparing the compressive support layer as described above, comprising the following steps: S1, internal mixing, preheating hydrogenated nitrile rubber and fluororubber to 120°C according to the formula proportions, then adding fumed SiO2 and carbon nanotubes and heating to 135°C to obtain internal mixing material; S2, compounding, adding anti-aging agent, peroxide vulcanizing agent, crosslinking agent, crosslinking agent, acid absorbent, and processing aid to the internal mixing material to obtain compounded material; S3, molding. S4, at 160-170℃ and injection pressure of 100-120MPa, the compression support layer is formed on the first metal skeleton ring to obtain the prefabricated sealing ring; S5, two-stage vulcanization, the prefabricated sealing ring is first vulcanized at 170-175℃ for 10-15min, and then vulcanized at 180℃ to 200-220℃ to obtain the rough sealing ring; S6, post-treatment, the rough sealing ring is surface treated to obtain the compression support layer.

[0013] In one optional embodiment, the carbon nanotubes in S1 are subjected to plasma treatment under a nitrogen atmosphere for no less than 5 minutes.

[0014] In one optional embodiment, the torque value of the kneaded material in S1 ranges from 25 to 30 N·m.

[0015] In one optional embodiment, the first stage of vulcanization in S4 is carried out by flat plate hot pressing, and the second stage of vulcanization is carried out by a blower oven.

[0016] Thirdly, this disclosure also provides an electrolytic cell that uses the sealing ring for electrolytic cells as described above, wherein the electrolytic cell includes either an AEM electrolytic cell or a PEM electrolytic cell.

[0017] The beneficial effects of this invention are that the ultra-high pressure sealing ring and its preparation method in this electrolytic cell establish a blend system with hydrogenated nitrile rubber and fluororubber as the matrix material, which takes into account both the hydrogen bond crosslinking network and the corrosion resistance of the fluorocarbon chain. The segmented vulcanization process can control the crosslinking density, so that the pressure-resistant support layer forms a uniform gradient change. Through the double-layer structure, the sealing bonding layer achieves a tight fit with the metal skeleton ring and improves the chemical corrosion resistance. At the same time, the pressure-resistant support layer and the sealing bonding layer use the elastic force generated by the elastic deformation of the cavity between the pressure and the metal skeleton layer to cancel out the external pressure. The pressure-resistant support layer, as the outermost structure, appropriately reduces the hardness to enhance the bonding effect with the sealing bonding layer, thereby meeting the working adaptability under ultra-high pressure of 70MPa.

[0018] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention are realized and obtained through the structures particularly pointed out in the description and the drawings.

[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description

[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0021] Figure 1 This is a front view of a sealing ring for an electrolytic cell provided in an embodiment of this disclosure;

[0022] Figure 2 A cross-sectional view of a sealing ring for an electrolytic cell provided in an embodiment of this disclosure;

[0023] Figure 3 A graph showing the relationship between sealing performance and pressure variation provided in the embodiments of this disclosure;

[0024] Figure 4 A sealing performance versus cycle count curve provided for embodiments of this disclosure;

[0025] Figure 5 A diagram showing the leakage rate fluctuation range provided in this embodiment of the disclosure;

[0026] Figure 6 A surface roughness Ra growth diagram provided for embodiments of this disclosure.

[0027] In the picture:

[0028] 1. First metal skeleton ring; 2. Compression-resistant support layer; 3. Sealing and bonding layer; 4. Small electrode plate; 5. Large electrode plate; 6. Second metal skeleton ring. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] As used herein, the phrases “in one embodiment,” “according to one embodiment,” “in some embodiments,” etc., generally refer to the fact that a particular feature, structure, or characteristic following the phrase can be included in at least one embodiment of this disclosure. Therefore, a particular feature, structure, or characteristic can be included in more than one embodiment of this disclosure, such that these phrases do not necessarily refer to the same embodiment. As used herein, the terms “example,” “exemplary,” etc., are used to “serve as an example, instance, or illustration.” Any implementation, aspect, or design described herein as “example” or “exemplary” is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. Rather, the use of the terms “example,” “exemplary,” etc., is intended to present concepts in a specific manner.

[0031] In this document, exemplary embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as “at least one of…” modify the entire list of elements when following a list of elements, rather than individual elements in the list. For example, the expression “at least one of a, b, and c” should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0032] The terminology used herein is for the purpose of describing specific exemplary configurations only and is not intended to be limiting. As used herein, the singular articles “a,” “an,” and “the” may also be intended to include plural forms unless otherwise clearly stated herein. The terms “comprising,” “including,” and “having” are inclusive and thus specify the presence of features, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or combinations thereof. The method steps, processes, and operations described herein should not be construed as requiring them to be performed in the specific order discussed or shown, unless specifically identified as such. Additional or alternative steps may be employed.

[0033] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0034] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0035] In this paper, PEM (Proton Exchange Membrane) electrolyzer refers to a proton exchange membrane electrolyzer; AEM (Anion Exchange Membrane) electrolyzer refers to anion exchange membrane electrolyzer.

[0036] Please see Figure 1 and Figure 2 ,like Figure 1 and Figure 2 As shown, this disclosure provides a sealing ring for an electrolytic cell, comprising: a first metal skeleton ring and a pressure-resistant support layer wrapped around its surface; the inner ring of the pressure-resistant support layer is embedded with a stacked sealing bonding layer and a small electrode plate; a second metal skeleton ring is wrapped inside the sealing bonding layer; the small electrode plate and a large electrode plate disposed on one side of the metal skeleton ring clamp and fix the sealing bonding layer; wherein the hardness of the pressure-resistant support layer is in the range of 65-75 Shore A; the pressure-resistant support layer comprises the following components by mass: 60 parts hydrogenated nitrile rubber, 40 parts fluororubber, 10-15 parts fumed SiO2, 3-5 parts carbon nanotubes, 1.5-2.5 parts peroxide vulcanizing agent, 2-3 parts crosslinking agent, and 2-5 parts processing aid; the hardness of the sealing bonding layer is not less than 85 Shore A.

[0037] In some embodiments, specifically, the hardness range of the sealing adhesive layer is 85-95 Shore A; the sealing adhesive layer comprises the following components by weight: 55 parts hydrogenated nitrile rubber, 45 parts fluororubber, 20-30 parts fumed SiO2, 4-8 parts carbon nanotubes, 1-3 parts anti-aging agent, 2.5-3.5 parts peroxide vulcanizing agent, 3-5 parts co-crosslinking agent, 1-3 parts crosslinking agent, 3-8 parts acid absorbent, and 0.5-2 parts processing aid.

[0038] In some embodiments, specifically, the thickness ratio of the compressive support layer to the sealing adhesive layer is not less than 3:1.

[0039] In some embodiments, specifically, the hydrogenation degree of the hydrogenated nitrile rubber is not less than 94%, wherein the acrylonitrile content is not less than 34%, and the Mooney viscosity ML(1+4) at 100°C is 40 to 60; the fluororubber includes vinylidene fluoride-hexafluoropropylene copolymer fluororubber with a fluorine content of not less than 66%.

[0040] In some embodiments, specifically, the anti-aging agent includes a 2,2,4-trimethyl-1,2-dihydroquinoline polymer, the acid absorbent includes highly active magnesium oxide, and the processing aid includes perfluoropolyether oil.

[0041] This disclosure also provides a method for preparing the compressive support layer as described above, comprising the following steps: S1, mixing: preheating hydrogenated nitrile rubber and fluororubber to 120°C according to the formula proportions, then adding fumed SiO2 and carbon nanotubes and heating to 135°C to obtain a mixed material; S2, compounding: adding anti-aging agent, peroxide vulcanizing agent, crosslinking agent, crosslinking agent, acid absorbent, and processing aid to the mixed material to obtain a compound; S3, molding: molding the compressive support layer on a first metal skeleton ring at 160-170°C and an injection pressure of 100-120 MPa to obtain a pre-made sealing ring; S4, two-stage vulcanization: first, the pre-made sealing ring is held at 170-175°C for 10-15 minutes for primary vulcanization, and then slowly heated to 200-220°C at 180°C for post-vulcanization to obtain a rough sealing ring; S5, post-treatment: surface treating the rough sealing ring to obtain the compressive support layer.

[0042] In some embodiments, specifically, the carbon nanotubes in S1 are subjected to plasma treatment under a nitrogen atmosphere for no less than 5 minutes.

[0043] In some embodiments, specifically, the torque value of the mortar in S1 ranges from 25 to 30 N·m, and the material is discharged after the torque value is met.

[0044] In some embodiments, specifically, in S4, the first stage of vulcanization is carried out by flat plate hot pressing, and the second stage of vulcanization is carried out by a blower oven.

[0045] This disclosure also provides an electrolytic cell that uses the sealing ring for electrolytic cells as described above, wherein the electrolytic cell includes any one of an AEM electrolytic cell and a PEM electrolytic cell.

[0046] In this embodiment, the specific information of each component is as follows:

[0047] Hydrogenated nitrile butadiene rubber: degree of hydrogenation (94%), Mooney viscosity ML (1+4) at 100℃ between 40-60, acrylonitrile content approximately 34%; purchased from Shanghai Zannan Technology Co., Ltd., ZN-35158.

[0048] Fluororubber: Vinylidene fluoride-hexafluoropropylene copolymer fluororubber (FKM, G-801, Daikin, Japan), with a fluorine content of 66%, is resistant to strong acids and oxidizing media and has low gas permeability. Hydrogenated nitrile rubber and fluororubber are preferably blended in a ratio of 55:45 as the matrix material.

[0049] The reinforcing filler used was hydrophobic fumed silica (Aerosil R812, Evonik, Germany, with a specific surface area of ​​approximately 260 m²). 2 / g, with a particle size of about 12nm) and plasma-modified carbon nanotubes (CNTs, Chengdu Institute of Organic Chemistry, Chinese Academy of Sciences, with a diameter of 10-20nm, a length of 10-30μm, and a conductivity of >100S / cm).

[0050] The processing aid used is perfluoropolyether oil (Fomblin Y-LVAC 06 / 6, Solvay, Belgium, molecular weight approximately 3,000 g / mol, viscosity approximately 30 cSt) to improve flowability.

[0051] The vulcanization system includes di-tert-butyl peroxide (DCP, Shanghai Macklin, purity ≥98%), triallyl isocyanurate (TAIC, Japan Mitsubishi Chemical), and trimethylolpropane triacrylate (TMPTMA, France Sartomer).

[0052] Specifically, the formulation of the sealing bonding layer is shown in Table 1.

[0053] Table 1

[0054]

[0055]

[0056] Specifically, the performance of each component in Table 1 was tested, and the results are shown in Table 2.

[0057] Table 2

[0058]

[0059]

[0060] Test method: Compression set test was conducted according to ISO 815-1:2008. The specimen was compressed by 25% at room temperature (23±2℃) or high temperature, held for 24 hours, and the residual deformation was measured.

[0061]

[0062] Where t0, tr, and ts represent the initial, recovered, and compressed thicknesses, respectively. This method is suitable for evaluating the elastic recovery properties of rubber materials.

[0063] Test results: Compressive permanent deformation rate at 70 MPa.

[0064] Analysis of 27 sets of orthogonal experimental data shows that the synergistic reinforcing system of CNTs and SiO2 significantly improves the performance of HNBR / FKM composite rubber. As the CNT addition amount increases from 4 phr to 8 phr, the tear strength significantly improves, rising from 22.0 kN / m to a maximum of 27.3 kN / m; simultaneously, the compression set decreases from 26% to a minimum of 18%, demonstrating excellent elastic recovery.

[0065] Increasing the fumed SiO2 content in the range of 20–30 phr helps to further enhance the material hardness, enabling Shore A to reach a hardness of over 90, thus meeting the rigidity requirements of high-pressure sealing rings.

[0066] In addition, increasing the dosage of DCP as a peroxide vulcanizing agent from 2.5 phr to 3.5 phr can effectively improve the crosslinking density and further reduce the compression set.

[0067] The optimal formulation is the combination of CNTs at 8 phr, SiO2 at 30 phr, and DCP at 3.5 phr. This formulation not only has high tear strength and low compression set, but also excellent hardness and overall mechanical properties, which is the preferred embodiment 27 for the sealing bonding layer.

[0068] Specifically, the formulation of the compressive support layer is shown in Table 3.

[0069] Table 3

[0070]

[0071]

[0072] Specifically, the performance of each component in Table 3 was tested, and the results are shown in Table 4.

[0073] Table 4

[0074]

[0075] Specifically, through orthogonal experimental analysis, the optimal formulation combination was determined to be HNBR 60 phr, FKM 40 phr, fumed SiO2 15 phr, CNTs 5 phr, perfluoropolyether oil 5 phr, DCP 1.5 phr, and TAIC 2 phr, i.e., Example 18. This combination exhibited the lowest compression set (15%) in the simulated data, while maintaining high hardness (65-70 Shore A) and good tear strength (48 kN / m). Experimental results showed that perfluoropolyether oil and TAIC had the most significant impact on compression set; low TAIC (2 phr) and high perfluoropolyether oil (5 phr) effectively reduced deformation, while high CNTs (5 phr) and moderate SiO2 (15 phr) helped maintain hardness.

[0076] The preferred embodiment 27 of the compression support layer is combined with the preferred embodiment 18 of the sealing bonding layer. The preparation method of the compression support layer includes the following steps: S1, internal mixing: hydrogenated nitrile rubber and fluororubber are preheated to 120°C according to the formula proportions, followed by the addition of fumed SiO2 and carbon nanotubes, and the temperature is raised to 135°C to obtain the internally mixed material; S2, compounding: anti-aging agent, peroxide vulcanizing agent, crosslinking agent, crosslinking agent, acid absorbent, and processing aid are added to the internally mixed material to obtain the compound. S3, Molding: The compressive support layer is formed on the first metal skeleton ring at 160-170℃ and injection pressure of 100-120MPa to obtain a pre-made sealing ring; S4, Two-stage vulcanization: The pre-made sealing ring is first vulcanized at 170-175℃ for 10-15 minutes, and then vulcanized at 180℃ to 200-220℃ to obtain a rough sealing ring; S5, Post-treatment: The rough sealing ring is surface-treated to obtain a compressive support layer.

[0077] Among them, carbon nanotubes were treated with 50W plasma for 5 minutes in a nitrogen atmosphere.

[0078] The performance of traditional O-rings, metal-reinforced sealing rings, and electrolytic cell sealing rings (double-layer sealing rings) obtained in the above embodiments were tested.

[0079] Please see Figures 3-6 ,like Figures 3-6 As shown, the double-layer sealing ring provided by the present invention... Figure 3 The leakage rate did not change significantly before the pressure reached 70 MPa. Figure 4 It maintains its seal integrity for more than 5,000 cycles under a dynamic pressure of 70 MPa; Figure 5 The leakage rate fluctuation range is less than 0.02. Figure 6 The frictional force on the middle surface increases only from 0.3 to 0.5 before and after being compressed.

[0080] Specifically, the sealing ring for this electrolytic cell can meet the high sealing requirements of a 70MPa electrolytic cell, but it is also suitable for environments below 70MPa and 70-80MPa.

[0081] In summary, this electrolytic cell utilizes an ultra-high pressure sealing ring and its preparation method to establish a blend system using hydrogenated nitrile rubber and fluororubber as the matrix material, which balances the corrosion resistance of the hydrogen bond crosslinking network and the fluorocarbon chain. The segmented vulcanization process can control the crosslinking density, resulting in a uniform gradient change in the pressure-resistant support layer. The double-layer structure utilizes the sealing bonding layer to achieve a tight fit with the metal skeleton ring and improve chemical corrosion resistance. At the same time, the elastic force generated by the elastic deformation of the pressure-resistant support layer and the sealing bonding layer under pressure cancels out the external pressure. The pressure-resistant support layer, as the outermost structure, has appropriately reduced hardness to enhance the bonding effect with the sealing bonding layer, thus meeting the working adaptability under ultra-high pressure of 70MPa.

[0082] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A sealing ring for an electrolytic cell, characterized in that, include: The first metal skeleton ring and the compressive support layer wrapped around its surface; The inner ring of the compressive support layer is embedded with a stacked sealing bonding layer and a small electrode plate; A second metal skeleton ring is wrapped inside the sealing and bonding layer; The small electrode plate and the large electrode plate disposed on one side of the metal frame ring are clamped together to fix the sealing bonding layer; wherein The hardness range of the compressive support layer is 60–75 Shore A; The compressive support layer comprises the following components by mass parts: Hydrogenated nitrile rubber 60 parts, fluororubber 40 parts, fumed SiO2 10-15 parts, carbon nanotubes 3-5 parts, peroxide vulcanizing agent 1.5-2.5 parts, crosslinking agent 2-3 parts, processing aid 2-5 parts; The hardness of the sealing bonding layer is not less than 85 Shore A.

2. The sealing ring for an electrolytic cell as described in claim 1, characterized in that, The hardness range of the sealing bonding layer is 85–95 Shore A; The sealing bonding layer comprises the following components by weight: 55 parts hydrogenated nitrile rubber, 45 parts fluororubber, 20-30 parts fumed SiO2, 4-8 parts carbon nanotubes, 1-3 parts anti-aging agent, 2.5-3.5 parts peroxide vulcanizing agent, 3-5 parts co-crosslinking agent, 1-3 parts crosslinking agent, 3-8 parts acid absorbent, and 0.5-2 parts processing aid.

3. The sealing ring for an electrolytic cell as described in claim 1, characterized in that, The thickness ratio of the compression-resistant support layer to the sealing bonding layer is not less than 3:

1.

4. The sealing ring for an electrolytic cell as described in claim 1, characterized in that, The hydrogenated nitrile rubber has a hydrogenation degree of not less than 94%, wherein the acrylonitrile content is not less than 34%, and the Mooney viscosity ML(1+4) at 100°C is 40-60. The fluororubber includes vinylidene fluoride-hexafluoropropylene copolymer fluororubber with a fluorine content of not less than 66%.

5. The sealing ring for an electrolytic cell as described in claim 1, characterized in that, The anti-aging agent includes a 2,2,4-trimethyl-1,2-dihydroquinoline polymer, the acid absorbent includes highly active magnesium oxide, and the processing aid includes perfluoropolyether oil.

6. A method for preparing a compressive support layer as described in claim 1, characterized in that, Includes the following steps: S1, internal mixing: hydrogenated nitrile rubber and fluororubber are preheated to 120°C according to the formula parts, and then gaseous SiO2 and carbon nanotubes are added and the temperature is raised to 135°C to obtain the internal mixing material. S2, mixing: anti-aging agent, peroxide vulcanizing agent, crosslinking agent, crosslinking agent, acid absorbent, and processing aid are added to the mortar to obtain the mixed material; S3, molding: The compression support layer is molded on the first metal skeleton ring at 160-170℃ and injection pressure of 100-120MPa to obtain the prefabricated sealing ring. S4, two-stage vulcanization: the pre-made sealing ring is first vulcanized at 170-175℃ for 10-15 minutes, and then the temperature is slowly increased from 180℃ to 200-220℃ for post-vulcanization to obtain the coarse sealing ring. S5, post-processing, involves surface treatment of the rough sealing ring to obtain a compressive support layer.

7. The preparation method according to claim 6, characterized in that, The carbon nanotubes in S1 are subjected to plasma treatment under a nitrogen atmosphere for no less than 5 minutes.

8. The preparation method according to claim 6, characterized in that, The torque value of the mortar in S1 ranges from 25 to 30 N·m.

9. The preparation method according to claim 6, characterized in that, In S4, the first stage of vulcanization is carried out by hot pressing on a flat plate, and the second stage of vulcanization is carried out by a blower oven.

10. An electrolytic cell, characterized in that, The sealing ring for the electrolytic cell as described in any one of claims 1-5 is used, wherein the electrolytic cell includes any one of an AEM electrolytic cell and a PEM electrolytic cell.